Komunikasi Efektif dalam Pendidikan Jasmani, Kesehatan dan Rekreasi melalui Penggunaan Bahasa - Ika Febriana; Aisyah Rahmahani; Edi Berkat Zai; Muhammad Arif Fadly; Sundari Ramahsita (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The use of good language has a significant influence on the learning process, including PJOK learning, because it can help teachers and students communicate more easily. Indonesian is one of the languages ​​that can be used in PJOK learning. The purpose of this study was to determine effective communication in Physical Education, Health and Recreation through the use of Language. A survey approach was used in this study, and Google Form was used to collect data. The findings of the study show how important Indonesian is in the learning process because it not only makes it easier for students to understand the material taught by the teacher, but also encourages them to actively participate, communicate, and interact with each other.